Effects of cobalt loading, particle size, and calcination condition on Co/CNT catalyst performance in Fischer-Tropsch reactions - Akbarzadeh, O. (2019)
The strong electrostatic adsorption (SEA) method was applied to the synthesis of a cobalt (Co) catalyst on a multi-walled carbon nanotube (CNT) support. In order to uptake more of the cobalt cluster with higher dispersion, the CNT was functionalized via acid and thermal treatment. The Co/CNT catalyst samples were characterized by a range of methods including the Brunauer-Emmet-Teller (BET) surface area analyzer, transmission electron microscopy (TEM), X-ray powder diffraction (XRD) analysis, atomic absorption spectroscopy (AAS), and H2-temperature programmed reduction (H2-TPR) analysis. The data from the TEM images revealed that the catalyst was highly dispersed over the external and internal walls of the CNT and that it demonstrated a narrow particle size of 6-8 nm. In addition, the data from the H2-TPR studies showed a lower reduction temperature (420 Â°C) for the pre-treated catalyst samples. Furthermore, a Fischer-Tropsch synthesis (FTS) reaction was chosen to evaluate the Co/CNT catalyst performance by using a fixed-bed microreactor at different parameters. Finally finding the optimum value of the cobalt loading percentage, particle size, and calcination conditions of Co/CNT catalyst resulted in a CO conversion and C5+ selectivity of 58.7 and 83.2, respectively. Â© 2018 by the authors.